APAKAH MODEL PEMBELAJARAN DENGAN MIND MAPPING DAPAT MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR ? - I Ketut Suardika; Abindarda Abindarda; Sakka Hasan (JRPD (Jurnal Riset Pendidikan Dasar), 2020)
Mind mapping is essential in shaping students' ability to think. In mind mapping, students are allowing sharing the thoughts they have learned into diagrams or patterns. The purpose of this study is to provide information about the feasibility of learning with a mind mapping model. In addition, this study will explain how the mind mapping learning model can improve student learning outcomes, especially elementary school students. This study uses a Classroom Action Research (CAR) design which divides the implementation phase into two cycles. The research location is located in the 96 Elementary School in Kendari City with the research subject of class Vb. Topic subjects used were "Beauty of Diversity In My Country". The research process using CAR which consists of planning, action, observation, evaluation, and reflection. The types of data generated are qualitative and quantitative, which are obtained through observation and tests of learning outcomes. The study reported that in the first cycle, there are 16 of the 23 students who have achieved the percentage of classical completeness or 69.57% with an average value of student learning outcomes is 75.88. Whereas in the second cycle there was an increase, namely there were 21 out of 23 students who had reached the percentage of completeness of learning or 91.30% with an average value of student learning outcomes was 87.43. These results identify that there is an increase in learning outcomes at each cycle by applying mind mapping in learning. Therefore, the use of mind mapping in learning, especially in elementary schools, is highly recommended to form student cognitive.